P764 Getting to the bottom of it: sexual positioning and syphilis stage at diagnosis among men who have sex with men. (14th July 2019) - Cornelisse, Vincent; Chow, Eric; Latimer, Rosie; Towns, Janet; Chen, Marcus; Bradshaw, Catriona; Fairley, Christopher
Abstract : Background: Effective syphilis control could be achieved by reducing its duration of infectiousness, for example, by identifying a higher proportion of cases at the primary stage. We hypothesised that men who have sex with men (MSM) who practice receptive anal intercourse ("bottoms") are more likely to miss the primary stage and present with secondary syphilis, compared to MSM who practice exclusively insertive anal intercourse ("tops"). Methods: This was a retrospective analysis of MSM diagnosed with either primary or secondary syphilis at Melbourne Sexual Health Centre between 2008 and 2017. We analysed associations between the stage of syphilis (primary vs secondary) and sexual behaviour data collected by computer-assisted self-interview (CASI). Results: 559 MSM diagnosed with syphilis provided sufficient behavioural data for analysis, of whom 338 (60%) had primary syphilis and 221 (40%) had secondary syphilis. Among "tops", 77% (95%CI 69–84) presented with primary syphilis and 23% (95%CI 16–31) presented with secondary syphilis. Whereas among "bottoms", 54% (95%CI 49–59) presented with primary syphilis and 46% (95%CI 41–51) presented with secondary syphilis. Among those with primary syphilis, 247 (73%, 95%CI 68–78) had a penile chancre and 77 (23%, 95%CI 19–28) had an anal chancre. In multivariate logistic regression, "bottoms" were more likely to present with secondary syphilis than "tops" (aOR 3.90, p<0.001), after adjusting for age, HIV status, and condom use. Conclusion: "Bottoms" more often presented with secondary syphilis compared to "tops", and most MSM who presented with primary syphilis had penile chancres rather than anal chancres. This suggests that MSM who have receptive anal intercourse may be more likely to overlook anal syphilis chancres, perhaps because these are located inside their anal canal. These men may benefit from additional strategies to improve the recognition of anal chancres. Disclosure: No significant relationships.